O Instituto Nossa Senhora do Sagrado Coração e a formação de professores em Capanema – PR (1960-1981) - Dagostin, Julia Eduarda (2024)
This dissertation, which is part of the Postgraduate Course in Education at Unioeste, Campus Francisco Beltrão - PR, in the line of research Society, Knowledge and Education, has as its central object the training of teachers at the Padre Cirilo Regional Normal School and the São José State Collegiate Normal School, which operated at the Nossa Senhora do Sagrado Coração Institute, in Capanema - PR, under the direction of the Daughters of Our Lady of the Sacred Heart. The first period, 1960, represents the installation of the religious sisters in Capanema - PR and the construction of the Nossa Senhora do Sagrado Coração Institute; the last period, 1981, covers the total disappearance of the normal high school course, according to the implementation of Law No. 5.692/1971. The aim of the research was to reconstruct the history of the Instituto Nossa Senhora do Sagrado Coração and the normal schools that operated there, the Escola Normal Regional Padre Cirilo and the Escola Normal Colegial Estadual São José, to understand the training of teachers in the municipality of Capanema - PR, from 1960 to 1981. The research was characterized as documentary, with a methodological perspective of dialectical analysis of direct written sources, such as yearbooks, chronicles of the religious community, photographs, tomb books, final class reports, among others, and oral sources, collected through semi structured interviews with students and others involved in the normal schools studied. The aim was to provide a historical overview, from the foundation of the Filhas de Nossa Senhora do Sagrado Coração to their educational work in Capanema - PR, the consequences of educational legislation and the expansion of the Normal School as a model for teacher training in Paraná and the Southwest region, highlighting the range of social relations involved in the creation, operation and closure of the institute. The aim was to provide a historical overview from the foundation of the Filhas de Nossa Senhora do Sagrado Coração to their educational work in Capanema - PR, the consequences of educational legislation and the expansion of the normal school as a model for teacher training in Paraná and the Southwest region, highlighting the range of social relations involved in the creation, operation and closure of the institute. From the results obtained, it is possible to conclude that teacher training in Capanema - PR was historically constituted in direct relation to state and national determinations on educational legislation and the general development of society, with the expansion of schooling and normal education in the Southwest Region strongly marked by the presence of the Filhas de Nossa Senhora do Sagrado Coração. The involvement of the sisters has meant a qualitative leap in the development of schools in Capanema - PR and has played an important role in local culture, education and evangelization. In addition to increasing the number of qualified teachers in Capanema - PR and the surrounding area, the two normal schools provided access to 1st and 2nd cycle secondary education in the area.